2019
DOI: 10.1007/s11187-019-00168-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender and bank lending after the global financial crisis: are women entrepreneurs safer bets?

Abstract: Using gender as a theoretical framework, we analyse the dynamics of bank lending to small and medium sized enterprises (SME) in the aftermath of the 2008 Global Financial Crisis. Using six waves of the SME Finance Monitor survey, we apply a formal Oaxaca-Blinder decomposition to test whether gender impacts upon the supply and demand for debt finance by women. Reflecting established evidence, we found women had a lower demand for bank loans; contradicting accepted wisdom however, we found that women who did app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 81 publications
4
65
1
1
Order By: Relevance
“…Following the 2008 financial crisis, one study concluded that women entrepreneurs dealt with the resulting recession in a defensive manner, while men used an offensive approach (Cesaroni et al, 2015). Another study of the global financial crisis found that women had lower demand for bank loans but were more successful, concluding that feminised risk aversion might inform the more conservative approach (Cowling et al, 2019). Alternatively, a comparative study of sole proprietors during the financial crisis showed women personally take care of house and family, and therefore, had more difficulty with work-family conflict and internal psychological balance than their male peers (Cesaroni et al, 2018).…”
Section: Business Models and Gendered Crisis Response: What Does The mentioning
confidence: 99%
“…Following the 2008 financial crisis, one study concluded that women entrepreneurs dealt with the resulting recession in a defensive manner, while men used an offensive approach (Cesaroni et al, 2015). Another study of the global financial crisis found that women had lower demand for bank loans but were more successful, concluding that feminised risk aversion might inform the more conservative approach (Cowling et al, 2019). Alternatively, a comparative study of sole proprietors during the financial crisis showed women personally take care of house and family, and therefore, had more difficulty with work-family conflict and internal psychological balance than their male peers (Cesaroni et al, 2018).…”
Section: Business Models and Gendered Crisis Response: What Does The mentioning
confidence: 99%
“…Kuschel and Lepeley (2016) argue that some investors (e.g., public funds, business angels, venture capitalists) might not fund women-led startups because of the potential for the leader to become pregnant and make the startup a lower priority, at least temporarily. However, recent studies conducted after the global financial crisis show that women may be less risky loan payers and therefore safer bets for financial institutions (Cowling et al 2019). Women are found to be more successful at raising money in crowdfunding platforms, as they seem to be better communicators (Gorbatai and Nelson 2015).…”
Section: Institutional Levelmentioning
confidence: 99%
“…There is a wide literature in the field of entrepreneurship that investigates whether the manager's gender is a major factor affecting firms' inclination to access bank credit, as well as whether lenders behave differently when providing loans to male and female borrowers. Most of these papers, however, provide mixed evidence on the existence of gender issues in access to finance (Rostamkalaei et al, 2018), and are usually focused on single concerns (such as borrower discouragement to apply for bank loans, and loan rejection perpetrated by the lenders) or investigate the behavior of SMEs chartered in specific countries (see, for example, Cowling et al, 2019;Presbitero et al, 2014). Hence, more comprehensive and more conclusive studies on the problems faced by SMEs when accessing bank lending are still needed by policy-makers, especially because of the acknowledged importance of small businesses for the real economy in Europe.…”
Section: Hypothesesmentioning
confidence: 99%
“…Third, the vast majority of existing studies tend to focus on single issues, rather than jointly considering a range of reasons, arising from the demand or the supply side of the bank lending market. In this regard, it is worth mentioning that most scholars in the field have investigated the issue of borrower discouragement to apply for bank loans, and loan rejection perpetrated by the lenders (see, for example, Cowling, Marlow, & Liu, 2019;Moro et al, 2017;Presbitero, Rabellotti, & Piras, 2014). What is missing, though, to the best of our knowledge, is a study that jointly assesses a variety of motivations (from the borrowers' perspective) not to apply for loans, as well as a range of adverse outcomes (of applications for bank lending) experienced by the SMEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation